PENERAPAN KURIKULUM MERDEKA BELAJAR PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Faizal Adi Nugroho; Sukari Sukari; Lailla Hidayatul Amin (Raudhah - Proud To Be Professional, 2024)
FAIZAL ADI NUGROHO, Thesis on the Application of the Independent Learning Curriculum in Islamic Religious Education Subjects at Muhammadiyah Imam Syuhodo Wonorejo Middle School, Polokarto District, Sukoharjo Regency, Academic Year 2023/2024, Dirasah Islamiyah IIM Surakarta 2024 This research focuses on the Independent Learning Curriculum, a new policy launched by Minister Nadiem Makarim. This curriculum aims to encourage learning that suits students' abilities and develop innovative learning methods to improve graduates' abilities. Several junior high schools (SMP) have just implemented this curriculum. Muhammadiyah Imam Syuhodo Middle School is one of the schools that has implemented the Independent Learning Curriculum in Islamic Religious Education (PAI) learning. This school must pay attention to the procedures used to implement it. The aim of this research is to find out how the Independent Learning Curriculum is implemented at Muhammadiyah Imam Syuhodo Middle School in Islamic Religious Education subjects, what are the results of implementing the Independent Learning Curriculum and the factors that support and hinder the implementation of the Independent Learning Curriculum are also studied. This type of research is qualitative research with a field approach in the form of descriptive narrative with an emphasis on collecting data from questionnaires, interviews and documentation, while the data analysis technique uses data reduction, data presentation and Hiberman's conclusion drawing. The results of this research are (1) The Independent Learning Curriculum implemented by PAI (syariah or fiqh) teachers at AMuhammadiyah Imam Syuhodo Middle School has been successfully implemented. This can be seen from the concept of an independent curriculum which is provided informatively both online and offline. Second, create an Educational Unit Operational Curriculum (KOSP), third create a Flow of Learning Objectives (ATP), and fourth create a teaching module for the Pancasila student strengthening project. Learning is carried out using various methods that are adapted to the teaching material. (2) Results obtained from the implementation of the Independent Learning Curriculum in Class VII Islamic Religious Education Subjects at Muhammadiyah Imam Syuhodo Middle School, namely: There is development of student competence through flexible learning, Achievement of Goals Learning through cultivating the Pancasila Student Profile which is also starting to develop, and (3) Implementation of the Independent Learning Curriculum in PAI (syariah/fiqh) subjects, of course there are several influencing factors, including supporting factors and inhibiting factors.